THE INFLUENCE OF ELECTRONIC WORD OF MOUTH (eWOM) AND BRAND TRUST ON PURCHASE INTENTION OF AQUA PRODUCTS AMONG GENERATION Z AFTER THE BOYCOTT: A CASE STUDY ON MANAGEMENT STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, UNIVERSITY OF UTARA SUMATRA - Sri Sarah br G.Manik; Alfifto; Amrin Mulia Utama Nst; Eka Dewi Setia Tarigan; Irwansyah Putra (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of Electronic Word of Mouth (eWOM) and Brand Trust on Purchase Intention for Aqua products following the emergence of a boycott issue. A boycott brand can influence consumer perceptions and purchasing decisions; Therefore, it is important to examine the role of electronic communication and brand trust in shaping consumer purchasing intentions. This research adopts a quantitative approach, with data collected through questionnaires and analyzed using multiple linear regression tests. The results show that, partially, eWOM has a positive and significant influence on the purchase intention of Aqua products. Similarly, Brand Trust is also proven to have a positive and significant partial effect. Simultaneously, both independent variables significantly and positively affect purchase intention after the boycott issue. These findings indicate that effective digital communication strategies and efforts to build and maintain brand trust are key to sustaining consumer loyalty, especially in the face of reputation crises.